2021
DOI: 10.1071/an20323
|View full text |Cite
|
Sign up to set email alerts
|

Mature herbs as supplements to ruminant diets: effects on in vitro ruminal fermentation and ammonia production

Abstract: Context High concentrations of crude protein in ruminant diets may lead to excessive production of ruminal ammonia, which may stress the animal’s metabolism and impact nitrogen efficiency. This may become a problem in zero-concentrate feeding systems when pasture grass is rich in crude protein. Polyphenols such as tannins may protect part of dietary protein from ruminal degradation and thus inhibit ammonia formation. Aims The present study screened mature herbs for their potential to mitigate ruminal ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Hamacher et al [ 10 ] found a content of 65 g tannic acid equivalent kg −1 , but they did not report the plant phenological stages; in addition, the environmental conditions were very different to our study. Kapp-Bitter et al [ 31 ], found a content of 89.9 g kg −1 , like our result for Field in July, in fact they harvested the plants during the seed ripening stage.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Hamacher et al [ 10 ] found a content of 65 g tannic acid equivalent kg −1 , but they did not report the plant phenological stages; in addition, the environmental conditions were very different to our study. Kapp-Bitter et al [ 31 ], found a content of 89.9 g kg −1 , like our result for Field in July, in fact they harvested the plants during the seed ripening stage.…”
Section: Resultssupporting
confidence: 88%
“…No condensed tannins (CT) were detected in the investigated plant organs (leaves, peduncles, inflorescence) and locations. In a study on mature herbs, as a supplement to ruminant diet, CT were not detected in plantain [ 31 ], as in our results. Conversely, a CT content of 3 g kg −1 was found by Hamacher et al [ 10 ], the content being very low respect to other plant species under study as Onobrychis viciifolia (87.6 g kg −1 ).…”
Section: Resultssupporting
confidence: 82%
“…Sanguisorba minor is mentioned as a promising plant for methane reduction in dairy (Loza et al, 2021), gaining up to 33% reduction. Also reduction of ruminal ammonia production in cattle is described for this herb when fed to cattle (Kapp-Bitter et al, 2021). Other herbs with a similar effect were Galium verum L., Leontodon hispidus L., Lotus corniculatus L., Onobrychis viciifolia Scop., Plantago lanceolata L. (Kapp-Bitter et al, 2021).…”
Section: Resultsmentioning
confidence: 75%
“…Also reduction of ruminal ammonia production in cattle is described for this herb when fed to cattle (Kapp-Bitter et al, 2021). Other herbs with a similar effect were Galium verum L., Leontodon hispidus L., Lotus corniculatus L., Onobrychis viciifolia Scop., Plantago lanceolata L. (Kapp-Bitter et al, 2021). Yarrow Achillea millifolium is known for its wound healing properties and a study in rabbits (Jalali et al, 2012) confirmed that an extract of yarrow improved the quality of healing of burn wounds and reduced the amount of pathogens in these wounds.…”
Section: Resultsmentioning
confidence: 75%
“…The total annual yields of pastures that contain a greater proportion of legumes are generally higher than grass monocultures (Gultekin et al, 2021). Lotus species are recognized for their tolerance to acid soils and low natural soil fertility (Escaray et al, 2012), and in South America, legumes are currently being more widely adopted as an alternative to improve the quality and quantity of pasture in regions with acid soils (Kapp-Bitter et al, 2021). The objective of this research was to identify the existence of root exudation of organic acid in L. corniculatus germplasms subjected to toxic Al levels and investigate the effect of this mechanism on the Al content in the root tissue and in morphological parameters of plant development.…”
Section: Introductionmentioning
confidence: 99%